Shen Gua's empiricism - Zuo, Ya 1982- (Cambridge, Massachusetts Harvard University Asia Center, 2018)
"Describes the life of Shen Gua, a distinguished renaissance man in China whose writing included remarkable "scientific" discoveries. Reveals the connection between Shen's life as an active statesman and his empirical inquiries, and provides insights into the dynamics between science and politics in the age of Neo-Confucianism"--Provided by publisher.
Peripateting the world (1051-1063) -- Envisioning learning -- Measuring the world (1063-1075) -- Individuating things -- Reforming the world (1071-1075) -- Buffeted by the world (1075-1085) -- In the system (and then out) -- Brushtalking the world (1085-1095) -- Building a non-system -- Farewell to system -- Reverberating in the world (1100-1800).
Includes bibliographical references (pages 299-325) and index.
Keywords: Shen, Kuo -- 1031-1095.; Empiricism; Neo-Confucianism -- China -- History; Science -- Political aspects -- China; Scientists -- China -- Biography; Statesmen -- China -- Biography; China -- Intellectual life -- 960-1644.